State Capitalism in Russia: A Review Article (Part 2) - O. M. Zhuravlev; I. A. Matveev (Евразийская интеграция: экономика, право, политика, 2022)
The article reviews current scholarship and debates on state capitalism as well as studies of this phenomenon in Russia.Aim. This article aims to review current scholarly debates on state intervention in the Russian economy and identify key positions in this field.Tasks. In the second part of the article, we review the existing research on state capitalism in Russia.Methods. This article compares scholars’ positions and identifies divisions in the field.Results. In the second part of the article, we show that, since the early 2000s, Russia was widely seen as a paradigmatic case of the state’s return to interventionist policies. We demonstrate that the first wave of studies in the 2000s, with a few exceptions, considered state capitalism in Russia to be an instrument of patronage and rent-seeking. However, subsequent research questioned this claim. State capitalism in Russia was now seen as an instrument of solving social problems, particularly in monotowns, a geopolitical tool and a way of defending national sovereignty, as well as a vehicle for financialization.Conclusion. Multiple empirical studies of state capitalism in Russia published in the 2010s demonstrate its complexity and versatility. However, the results of empirical research are yet to be systematized and the Russian political economy still lacks a macro analysis that would consider all of its structural and institutional dimensions.